Single nucleotide polymorphisms and insertiondeletions for genetic markers and anchoring the maize FingerPrint Contig Physical Map - Vroh Bi, Irie; McMullen, M.; Sánchez Villeda, H.; Schroeder, S.; Gardiner, J.; Polacco, M.; Soderlund, C.; Wing, Rod A.; Fang, Z.; Coe, E. (Wiley, 2006)
Single nucleotide polymorphisms (SNPs) and insertion–deletions (InDels) are becoming important genetic markers for major crop species. In this study we demonstrate their utility for locating fingerprint contigs (FPCs) to the genetic map. To derive SNP and InDel markers, we amplified genomic regions corresponding to 3000 unigenes across 12 maize (Zea mays L.) lines, of which 194 unigenes (6.4%) showed size polymorphism InDels between B73 and Mo17 on agarose gels. The analysis of these InDels in 83 diverse inbred lines showed that InDels are often multiallelic markers in maize. Single nucleotide polymorphism discovery conducted on 592 unigenes revealed that 44% of the unigenes contained B73/Mo17 SNPs, while 8% showed no sequence variation among the 12 inbred lines. On average, SNPs and InDels occurred every 73 and 309 bp, respectively. Multiple SNPs within unigenes led to a SNP haplotype genetic diversity of 0.61 among inbreds. The unigenes were previously assigned to maize FPCs by overgo hybridization. From this set of unigenes, 311 (133 SNP and 178 InDel) loci were mapped on the intermated B73 × Mo17 (IBM) high-resolution mapping population. These markers provided unambiguous anchoring of 129 FPCs and orientation for 30 contigs. The FPC anchored map of maize will be useful for map-based cloning, for genome sequencing efforts in maize, and for comparative genomics in grasses. The amplification primers for all mapped InDel and SNP loci, the diversity information for SNPs and InDels, and the corresponding overgoes to anchor bacterial artificial chromosome (BAC) contigs are provided as genetic resources.